Analyzing Electronic Service Quality in Shopee Using the E-Servqual Method - Islan Mutiana Reva; Rizal Ramdan Padmakusumah (Logistic and Operation Management Research (LOMR), 2026)
This study evaluates the electronic service quality of the Shopee e-commerce platform using the e-servqual framework. The increasing use of digital commerce platforms has intensified the need for electronic service quality evaluation. A quantitative descriptive approach was employed involving 100 active Shopee users selected through purposive sampling. Data were collected through an online questionnaire and analyzed using descriptive e-servqual gap analysis and cartesian diagram. The analysis examined the gaps between users’ expectations and perceived service performance across seven dimensions: efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact. The findings indicate that all dimensions produced negative gap scores, suggesting that the platform’s service performance has not fully met user expectations. The largest negative gap was identified in the responsiveness dimension (-0.984), followed by system availability (-0.828) and privacy (-0.820). Cartesian analysis revealed that several attributes related to system stability, customer service responsiveness, compensation procedures, and information clarity were positioned in Quadrant I, indicating high importance but relatively low performance. These findings highlight several service attributes that require managerial attention and improvement. The study contributes empirical insights into the application of the e-servqual approach in the Indonesian e-commerce context based on a limited user sample.